Two-year apprenticeships - a successful model of training? - Kammermann, Marlise [Verfasser]; Stalder, Barbara E. [Verfasser]; Hättich, Achim [Verfasser] (My University, 2011)
"Educational policy is asked to support young people in their successful transition from education to employment. In Switzerland, a two-year apprenticeship with Federal VET Certificate was established in 2002 aimed at increasing the employability of low-achieving school leavers. It is a low-threshold VET programme offering standardised vocational training to low-achieving youths. It leads to a VET Certificate, which is different from the Federal VET Diploma obtained after a three- or four-year apprenticeship. Data of two Swiss longitudinal studies including a sample of apprentices on a two-year training course with either a special needs (N=28) or a regular school (N=261) background at lower secondary, and a sample of graduates on a three-year training course (N=118) are used to study the success of the two-year apprenticeship from a comparative perspective. The findings confirm that the new apprenticeship offers favourable learning opportunities that foster employability and upward mobility after graduation. However, the findings also indicate limitations of the two-year apprenticeship, such as the least successful learners can only profit from the new form of apprenticeship to a certain degree." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; P 1.7 Benachteiligte; I 2.2.1 Westeuropa; Zweijähriger Ausbildungsberuf; Benachteiligter Jugendlicher; Berufseinmündung; Zweite Schwelle; Evaluation; Empirische Untersuchung; Schweiz